Chemoenzymatic Production of Enantiocomplementary 2‐Substituted 3‐Hydroxycarboxylic Acids from l‐α‐Amino Acids. Issue 11 (31st March 2021) - Pickl, Mathias; Marín‐Valls, Roser; Joglar, Jesús; Bujons, Jordi; Clapés, Pere
Abstract: A two‐enzyme cascade reaction plus in situ oxidative decarboxylation for the transformation of readily available canonical and non‐canonical l ‐α‐amino acids into 2‐substituted 3‐hydroxycarboxylic acid derivatives is described. The biocatalytic cascade consisted of an oxidative deamination of l ‐α‐amino acids by an l ‐α‐amino acid deaminase from Cosenzaea myxofaciens, rendering 2‐oxoacid intermediates, with an ensuing aldol addition reaction to formaldehyde, catalyzed by metal‐dependent ( R )‐ or ( S )‐selective carboligases namely 2‐oxo‐3‐deoxy‐l ‐rhamnonate aldolase (YfaU) and ketopantoate hydroxymethyltransferase (KPHMT), respectively, furnishing 3‐substituted 4‐hydroxy‐2‐oxoacids. The overall substrate conversion was optimized by balancing biocatalyst loading and amino acid and formaldehyde concentrations, yielding 36–98% aldol adduct formation and 91–98% ee for each enantiomer. Subsequent in situ follow‐up chemistry via hydrogen peroxide‐driven oxidative decarboxylation afforded the corresponding 2‐substituted 3‐hydroxycarboxylic acid derivatives. Abstract :